Management of in-Amphora “Trebbiano Toscano” Wine Production: Selection of Indigenous Saccharomyces cerevisiae Strains and Influence on the Phenolic and Sensory Profile - Simona Guerrini; Damiano Barbato; Silvia Mangani; Donatella Ganucci; Giacomo Buscioni; Viola Galli; Andrea Triossi; Lisa Granchi (Foods, 2023)
The use of earthenware amphorae in winemaking can give wines unique attributes enhancing their typicity. Therefore, in this study, spontaneous and inoculated in-amphora fermentations of Trebbiano Toscano grape must were monitored to assess the Saccharomyces cerevisiae strains occurring in each fermentation as well as the chemical characteristics of the wines. Strain typing via Interdelta analyses pointed out that the commercial starters did not dominate, showing 24% and 13% implantation percentages, and that 20 indigenous strains were present at different percentages, ranging from 2 to 20%, in inoculated and spontaneous fermentations. The assessment of the technical characteristics of the indigenous strains via fermentations at lab and pilot scale (20 L amphorae) and the sensory analysis of the experimental wines allowed for the selection of two indigenous strains to be used as starter cultures in comparison to a commercial strain in 300-L-amphorae vinifications in the cellar. The observed fermentative performances and sensory analysis of the experimental wines highlighted that one indigenous S. cerevisiae strain dominated the process and conferred distinctive sensory characteristics to the Trebbiano Toscano wine, demonstrating its effectiveness in managing the in-amphora fermentations. In addition, the results demonstrated the ability of amphorae to protect the polyphenolic compounds from oxidation during wine ageing. Indeed, the concentration of both hydroxycinnamic acids and flavonols decreased, with an average reduction of 30% and 14%, respectively, while hydroxybenzoic acids remained unchanged.